(untitled) (Journal of International Studies, 2017)
The concepts of ‘guanxi’ (relationships and networking) and ‘xinyong’ (interpersonal trust) in Chinese traditional ethics are often studied as the key factors that contribute to the pattern and succession of the ethnic Chinese in business practices which are based on the cultural approach. In the context of Southeast Asia such as in Indonesia, Malaysia, The Philippines, the ethnic Chinese are one of the minority groups whose profession is dominantly that of a businessman or an entrepreneur. As stated in the literature, even though the ethnic Chinese are classified as a minority group in those countries, some of the Chinese capitalist groups had controlled 70-80% of the private business sector. However, these two traditional concepts are not the only main factors of the Chinese business success, but the ‘irregular’ business pattern such as the patronage relationship with political elites also becomes the most important criteria. Hence, this study needed to re-examine and clarify whether the implementation of the guanxi and xinyong concepts in Chinese business activities are still relevant in their business practice due to the political connection in the Chinese business succession also being a dominant variable. This study was based on a fieldwork conducted in Indonesia especially in Medan City of Indonesia and used the descriptive qualitative method through interviews and library research. This aim of this study were three fold: the first was to discuss the relevance of the guanxi and xinyong concept in Chinese business practices, the second was to discuss whether the Chinese business practices were more influenced by a formal community organization or rather influenced by an informal network among Chinese businessmen through guanxi and xinyong bases, third, this study also discussed the challenges faced by the Chinese in attempting their business interests.